2009
DOI: 10.1165/rcmb.2008-0018oc
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Mixed Cystic Fibrosis and Normal Bronchial Epithelial Cell Cultures

Abstract: Cystic fibrosis (CF) airway epithelia exhibit altered Cl(-) and Na(+) transport properties and increased IL-8 secretion. In the present study, we examined whether a small proportion of cells with a normal phenotype could normalize the ion transport and IL-8 secretion properties of a CF airway epithelial cell layer. We obtained three types of primary cultures of human bronchial epithelial cells: one composed of 100% non-CF cells, one of 100% CF cells, and one of 10% non-CF and 90% CF cells ("cocultures"). Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
2
36
2
Order By: Relevance
“…2B). These data are consistent with results from human airway epithelia expressing either endogenous levels of CFTR or overexpressing CFTR (10)(11)(12)(13)(14). However, as the percentage of WT cells increased, Airway epithelia were generated with varying ratios of CFTR ΔF508/ΔF508 and CFTR +/+ cells.…”
Section: Hcosupporting
confidence: 87%
See 1 more Smart Citation
“…2B). These data are consistent with results from human airway epithelia expressing either endogenous levels of CFTR or overexpressing CFTR (10)(11)(12)(13)(14). However, as the percentage of WT cells increased, Airway epithelia were generated with varying ratios of CFTR ΔF508/ΔF508 and CFTR +/+ cells.…”
Section: Hcosupporting
confidence: 87%
“…n = 7-8. The * indicates the difference from epithelia with 100% WT cells by repeated measures ANOVA, P < 0.05. epithelium are WT or overexpress CFTR, Cl − secretion rises to the level of WT epithelia (10)(11)(12)(13)(14). However, knowledge that CFTR conducts HCO 3 − (48), that HCO 3 − is the major pH buffer of ASL (49), and that HCO 3 − secretion plays a key role in airway host defense (31)(32)(33)(34)(35)50) led us to test the relationship between CFTR expression and HCO 3 − secretion.…”
Section: Increasing Cftr Expression Progressively Enhances Asl Host Dmentioning
confidence: 99%
“…This suggests that the pathways underlying processing and recycling of CFTR may become saturated as the level of wtCFTR approaches 10%. This is also consistent with a recent study that showed normal ion transport properties and normalized IL-8 secretion in mixed cultures containing 90% CF and 10% non-CF human bronchial epithelial cells [34]. While it has been suggested that these observations indicate involvement of gap-junctional communication via connexins [35][36][37], the underlying mechanism that links wtCFTR function to IL-8 secretion is not known and further investigation will be required to dissect the pathways involved.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is known that CFTR constitutes a low-abundance mRNA in airway epithelia [30] a minor level of CFTR gene transfer to the airway epithelia is sufficient to correct the Cl − transport in vitro and in vivo [31]. Furthermore, only 10 % of normal cells are sufficient to normalize the main dysregulated parameters such as Cl − or Na + conductance and IL8 secretion [32].…”
Section: Discussionmentioning
confidence: 99%